2018
DOI: 10.1007/s12144-018-9901-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the roles of child temperament and teacher-child relationships as predictors of Turkish children’s social competence and antisocial behavior

Abstract: The present study examined the concurrent contribution of Turkish children's temperament and teacher-child relationship quality to their social competence and antisocial behavior, with a specific focus on the moderating role of digitalcommons.unl.edu behavior at higher levels of teacher-child conflict. In addition, at high levels of child shyness, social competence ratings improved as teacher-child closeness increased. Inhibitory control was positively correlated with social competence and negatively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…There is mounting evidence of associations between the STR and markers of preschool and elementary students’ self-regulation, compliance, social competence, and problem behaviors (Acar et al, 2018; Crockett, Wasserman, Rudasill, Hoffman, & Kalutskaya, 2018; Hamre et al, 2013; Maldonado-Carreño & Votruba-Drzal, 2011; Portilla, Ballard, Adler, Boyce, & Obradović, 2014; Williford, Vick Whittaker, Vitiello, & Downer, 2013). In addition, decades of research supports the premise that STR-quality is related to students’ emotional and behavioral engagement and academic achievement (Baker, Grant, & Morlock, 2008; Hernández et al, 2016; Hughes, Wu, Kwok, Villarreal, & Johnson, 2012; Maldonado-Carreno & Votruba-Drzal, 2011; McCormick, O’Connor, Cappella, & McClowry, 2013).…”
Section: Teachers As Socializing Agentsmentioning
confidence: 99%
“…There is mounting evidence of associations between the STR and markers of preschool and elementary students’ self-regulation, compliance, social competence, and problem behaviors (Acar et al, 2018; Crockett, Wasserman, Rudasill, Hoffman, & Kalutskaya, 2018; Hamre et al, 2013; Maldonado-Carreño & Votruba-Drzal, 2011; Portilla, Ballard, Adler, Boyce, & Obradović, 2014; Williford, Vick Whittaker, Vitiello, & Downer, 2013). In addition, decades of research supports the premise that STR-quality is related to students’ emotional and behavioral engagement and academic achievement (Baker, Grant, & Morlock, 2008; Hernández et al, 2016; Hughes, Wu, Kwok, Villarreal, & Johnson, 2012; Maldonado-Carreno & Votruba-Drzal, 2011; McCormick, O’Connor, Cappella, & McClowry, 2013).…”
Section: Teachers As Socializing Agentsmentioning
confidence: 99%
“…Previous studies have provided initial evidence that teacher-child closeness is a signi cant predictor of children's socioemotional competencies. 34 demonstrated that teacher-child closeness effectively protected and supported the social competence of children with high levels of shyness. For children in special education, high levels of teacher-child closeness were associated with better social, emotional and behavioural classroom adjustment 12 .…”
Section: Teacher-child Relationship and Children's Socioemotional Com...mentioning
confidence: 99%
“…In addition, we expected to find that low surgency and effortful control, and high negative affectivity, combined with high relationship conflicts would contribute to a higher initial level of and increase in internalizing problems (Hypothesis 3b-2). Finally, we expected to find that low surgency, low negative affectivity, and high effortful control combined with high relationship closeness would contribute to a higher initial level of and a lower decrease in prosocial behavior (Hypothesis 3b-3; e.g., Acar et al, 2020;Karreman et al, 2010;. Due to the associations of relationship quality and socioemotional functioning with achievement and parents' education, the control variables of GPA, as well as the mother's and father's education, were included in the final analyses (Hinshaw, 1992;Martin-Storey et al, 2018;Pakarinen et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%